Seasonal hydrology and fish assemblage structure in the floodplain of the lower Amazon River. Issue 2 (22nd September 2020) - Silva, Poliane B.; Arantes, Caroline C.; Freitas, Carlos E. C.; Petrere, Miguel; Ribeiro, Frank R. V.
Abstract: We investigated how the taxonomic and functional structures of fish assemblages in the lower Amazon River floodplain responded to seasonal hydrological variations. Fishes were sampled in 440 aquatic habitats across a floodplain area of 17, 673 km 2 during periods of high, receding, low and rising water. In addition, we recorded local environmental and landscape variables known to affect fish assemblages in floodplains. Redundancy analysis indicated that the taxonomic and functional structures of the fish assemblages were associated with water levels as well as local environmental, landscape and spatial variables. Our results showed that piscivores, planktivores and omnivores, as well as species with periodic and intermediate life history strategies, dominated the floodplain fish assemblages during periods of high‐water levels, whereas herbivores, invertivores and detritivores, as well as species of large body size with an equilibrium life history strategy, dominated the fish assemblages during periods of low‐water levels. Hydrology strongly influenced the structure of the fish assemblages in the Amazon floodplains. Our results indicate that the maintenance of seasonal hydrological dynamics in the basin is essential for the conservation of the regional fish diversity.